Factors Influencing the Intention to Obtain Accountant Certifications - Ayu Chairina Laksmi; Indah Suciati (The Indonesian Journal of Accounting Research, 2018)
Abstract: Professional accountant certification has many benefits for individual accountants as well as for the accounting profession in term of upscaling and increasing competitiveness. The purpose of this study is to examine the influence of attitude, subjective norms, and perceived behavior control on ACCA, CA and CPA professional accountant certifications and to understand students’ intention to those certifications. The data were analyzed using multiple linear regression analysis. The results show that attitude and subjective norms have a positive and significant effect on students' intention to obtain the professional accountant certifications. The results also show that perceived behavior control does not have any negative and significant effect on students’ intention, and the knowledge on those certifications does not have any positive and significant effect on students' intention. This study reveals the factors influencing students’ intention to get professional accountant certifications.Abstrak: Sertifikasi akuntan profesional memiliki banyak manfaat bagi akuntan individu maupun bagi profesi akuntansi dalam hal peningkatan dan peningkatan daya saing. Tujuan dari penelitian ini adalah untuk menguji pengaruh sikap, norma subyektif, dan kontrol perilaku yang dirasakan pada sertifikasi akuntan profesional ACCA, CA dan CPA dan untuk memahami niat siswa untuk sertifikasi tersebut. Data dianalisis menggunakan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa sikap dan norma subyektif memiliki pengaruh positif dan signifikan terhadap niat siswa untuk memperoleh sertifikasi akuntan profesional. Hasilnya juga menunjukkan bahwa kontrol perilaku yang dirasakan tidak memiliki pengaruh negatif dan signifikan terhadap niat siswa, dan pengetahuan pada sertifikasi tersebut tidak memiliki pengaruh positif dan signifikan terhadap niat siswa. Penelitian ini mengungkapkan faktor-faktor yang mempengaruhi niat siswa untuk mendapatkan sertifikasi akuntan profesional.